Panislamist and Pantyurkist Motion of Crimean Tatars at the Beginning of XX Century - V. I. Korolev (Проблемы постсоветского пространства, 2019)
A problem which is examined in the article before was not the article of scientific illumination. It served reason of appeal of author to the archived sources which are first entered in a scientific turn. Actuality of the article consists in that displays of panislamizm and pantyurkizm, having deep roots in the past, in one or another degree take place and now. Research is based on the documents of the Record Office of Republic Crimea, which were at one time geared-up Department of police and his Crimean structures. An author comes in to the conclusion, that in Crimea, as well as in other regions of the Russian empire, where a moslem population lived compact, panislamist and pantyurkist motion was got by development. This motion was headed the representatives of intelligentsia, well-off and influential persons. One of them was IsmaelGasprinskiy, leader of pantyurkist motion of all-russian scale. Panislamizm in Crimea was organizationally designed as organizations of «Conscience». This structure can be considered the first national political party of Crimean Tatars. Crimean pantyurkists and panislamists had regular connections with the centers of Russian, Turkish, Romanian moslem motions. The fact of organization of group of the Crimean national revolutionaries in the capital of Turkey deserves attention. It is the important certificate of the close interlacing revolutionary and panislamist activity.